Depressed mood: changes during a five-year follow-up in 75-year-old men and women in three Nordic localities - Heikkinen, Riitta-Liisa; Berg, Stig; Avlund, Kirsten; Tömäkangas, Timo (Aging clinical and experimental research, 2002)
The aim of the study was to look firstly at the changes that occurred in depressive symptomatology over a 5-year period among originally 75-year-old residents in three Nordic localities: Glostrup in Denmark, Göteborg in Sweden and Jyväskylä in Finland, and secondly, at some selected variables if they predicted depressed mood in this study. The study is a part of a 5-year follow-up of the Nordic comparative NORA study on functional capacity. A 5-year follow-up was carried out with the survivors in 1994. Depressive symptomatology was assessed by the Center for Epidemiologic Studies Depression Scale (CES-D). The number of survivors was 277 in Glostrup, 226 In Göteborg and 250 in Jyväskylä. The proportion of respondents with depressive symptoms was highest in Jyväskylä; this was true for both men and women at baseline and at the follow-up. In the baseline study, minor depression was more common among women than men in all three localities, and at the follow-up in Göteborg and Glostrup. In the follow-up study, men and women in Jyväskylä scored higher means on the CES-D scale than did the groups in Göteborg and Glostrup. During the follow-up, there was no significant change in the mean score describing depressed mood (CES-D total scale) in any locality in either men or women. The mean score of those who died during the follow-up period differed significantly from the score of survivors among women in Göteborg and in Glostrup. The most clear predictors for depressed mood in this Nordic 5-year follow-up study were chronic diseases, feelings of loneliness, and self-rated health.